2013
DOI: 10.1016/j.jbankfin.2013.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Product market power, industry structure, and corporate earnings management

Abstract: This is the first study to establish a link between product market power of firms and the degree of earnings management. We hypothesize and document a significant and robust association between (a) a firm's product market pricing power and its degree of earnings management, and (b) industry competitiveness and the degree of earnings management in the industry. Our study reveals that firms with inferior product market pricing power engage in greater discretionary earnings accruals, adding a new dimension to our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
149
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(165 citation statements)
references
References 80 publications
14
149
1
1
Order By: Relevance
“…A possible reason for the existence of significant differences between sectors is the level of competitiveness within them. According to Datta, Iskandar-Datta and Singh (2013), the companies operating in more competitive sectors are more likely to manage outcomes. Corroborating Datta et al (2013), Verrecchia and Weber (2006) found evidence that the level of transparency in sectors with greater competition decreases significantly.…”
Section: Based Onmentioning
confidence: 99%
See 2 more Smart Citations
“…A possible reason for the existence of significant differences between sectors is the level of competitiveness within them. According to Datta, Iskandar-Datta and Singh (2013), the companies operating in more competitive sectors are more likely to manage outcomes. Corroborating Datta et al (2013), Verrecchia and Weber (2006) found evidence that the level of transparency in sectors with greater competition decreases significantly.…”
Section: Based Onmentioning
confidence: 99%
“…According to Datta, Iskandar-Datta and Singh (2013), the companies operating in more competitive sectors are more likely to manage outcomes. Corroborating Datta et al (2013), Verrecchia and Weber (2006) found evidence that the level of transparency in sectors with greater competition decreases significantly. Besides competitiveness, Bagnoli and Watts (2010) indicate other factors related to sectoral characteristics which could influence the level of management of outcomes.…”
Section: Based Onmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have focused on determining whether earnings management exists and on identifying the motive for managing earnings (e.g. Anjum et al 2012;Brown & Higgins 2001;Caton et al 2011;Chang, Hsin & Hou 2013;Chiu et al 2013;Datta, Iskandar-Datta & Singh 2013;Degeorge et al 2013;Essid 2012;Farrell, Unlu & Yu 2014;Francoeur, Amar & Rakoto 2012;Habib, Bhuiyan & Islam 2013;Hansen 2010;He, Yang & Guan 2011;Jha 2013;Kangarluei, Motavasse & Abodllahi 2011;Karampinis & Hevas 2013;Kim & Sohn 2013;Lin & Wu 2014;Nagata 2013;Salteh & Valipour 2012;Shu & Chiang 2014;Wu, Lin & Fang 2012;Zhang & He 2013). lenders and creditors (or other categories of investors) with a method for analysing the value of enterprises.…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies have argued that companies active in the capital market, are more willing to disclose information (Lang & Lundholm, 1993, 2000Frankel et al, 1995;Healy et al, 1999;Healy & Palepu, 2001;Datta et al, 2013;de La Bruslerie & Gabteni, 2014). Therefore, managers usually try to provide more information and better understanding of the company's performance for external people, even in an efficient capital market (Francis et al, 2008).…”
Section: Introductionmentioning
confidence: 99%